The relationship between team mental models and group cohesion and collective efficacy - Kurden, Ayşe Yaren (My University, 2025)
Amaç: Bu çalışmada Takım Zihinsel Modelleri Ölçeği’nin (TZMÖ) psikometrik özelliklerinin ölçülmesi ve ölçeğin Türkçe uyarlamasının gerçekleştirilmesi amaçlanmıştır. Bu doğrultuda ilk aşamada ölçeğin Türkçe geçerlik güvenirlik çalışması yapılmıştır. Ayrıca ikinci çalışmada takım zihinsel modelleri ile takım sargınlığı ve kolektif yeterlik arasındaki ilişki incelenmiştir. Gereç ve Yöntem: Birinci çalışmaya uygun örnekleme yöntemi ile seçilmiş 18-30 yaş arası en az iki yıldır takım sporları ile uğraşan 103 kadın ve 209 erkek olmak üzere toplam 322 sporcu katılmıştır. Çalışmada veri toplama aracı olarak Filho vd. (2022) tarafından geliştirilen Takım Zihinsel Modelleri Ölçeği kullanılmıştır. Yakınsak geçerlilik için AVE ve CR değerleri, ıraksak geçerlilik için ise ASV ve MSV değerleri hesaplanmıştır. Ölçüt ilişkili geçerlilik için ise TZMÖ ile Grup Sargınlığı Ölçeği (GSÖ) ve Takım Sporlarında Paylaşılan Zihinsel Modeller Ölçeği (TSPZMÖ) arasındaki ilişki incelenmiştir. Güvenirlik için iç tutarlık katsayısı hesaplanmıştır. İkinci çalışma 218 katılımcı ile yürütülmüş ve ölçümlerde TZMÖ, Grup Sargınlığı Ölçeği ve Kolektif Yeterlik Ölçeği kullanılmıştır. Bulgular: DFA sonucuna göre TZMÖ’nin iki faktörlü yapısı desteklenmiş ve faktör yükleri .50 ile .77 arasında bulunmuştur. Uyum indeksleri X2/ df=2,868, GFI= ,945, AGFI= ,909, NFI=,922, CFI=,947 ve RMSEA= .076 olarak hesaplanmıştır. Ölçüt ilişkili geçerlilik için TSPZMÖ ve GSÖ ile pozitif ilişkili bulunmuştur. Sonuç: TZMÖ Türkçe formu geçerli ve güvenilir bir ölçek olarak Türk sporcu örnekleminde kullanılabilir.

Objective: It was aimed to determine psychometric properties of Team Mental Models Instrument (TMMI) and to adapt the instrument into Turkish population. In the first, the validity and reliability of Turkish version of Team Mental Models Instrument was examined. Furthermore, the second study investigated the connection between TMMs and collective efficacy and group cohesion. Materials and Methods: The convenience sampling method was applied in the first study. A total of … team sports participants between the ages of 18 and 30, who have at least two years sport experience participated in the study: 103 women and 209 males. Team Mental Models Instrument (Filho et al., 2022) was applied for the first study. For convergent validty, AVE and CR values and for convergent validtity the ASV and MSV values have been calculated. For criterion related validity, the relationship between Team Environment Questionnaire (TEQ) and Shared Mental Models Scale (SMMS) was examined. For reliability, internal consistency coefficient was calculated. 218 athletes who are over the ages of 18 who had played team sports for at least two years took part in the second study. Team Mental Models Instrument (TMMI), Group Environment Questionnaire (GEQ) and Collective Efficacy Scale (CES) were used. Results: According to the Confirmatory Factor Analysis (CFA) results, the two-factor structure of the Team Mental Models Instrument (TMMI) has been supported, with factor loadings ranging from .50 to .77. The fit indices were calculated as follows: X²/ df = 2.868, GFI = .945, AGFI=909, NFI = ,922, CFI = .947, and RMSEA = .076. For criterion related validity, the TMMI was found to be positively related to the (SMMS) and (GEQ). Conclusion: The Turkish version of the TMMI can be used as a valid and reliable scale in the Turkish sample.
Sporda takım zihinsel modellerinin grup sargınlığı ve kolektif yeterlik ile ilişkisinin değerlendirilmesi
Keywords: Athletes; collective efficacy; complementary mental models; group cohesion; grup sargınlığı; kolektif yeterlik; Psikolojik yönleri; Psychological aspects; shared mental models; Spor; Sporcular; Sports; takım zihinsel modelleri; Takım zihinsel modelleri ölçeği; team mental models; Team mental models instrument